The Effect of Free Writing Technique on Students’ Writing Skills at SMA Negeri 6 Kendari - Dewi, Sri Mustika; Suhartini, Lelly; Muhsin, Muh. Khusnun (Universitas Halu Oleo, 2021)
This study is conducted to examine whether there is any significant effect of Free writing technique on students' writing skills at X MIPA 1 in SMAN 6 Kendari or not. This research was conducted in pre-experimental research design. The population of this research was all the first grade science program students (X MIPA) of SMAN 6 Kendari. The total of population was 207 students which consisted of 6 classes. The sample of this research was X MIPA 1 which consists of 35 students. The data of this research were collected by giving the students pre-test and post-test in the form of written test that related to the topic of Recount Text. Then, the data were analyzed by using SPSS 17.0 version and used descriptive analysis and inferential statistics. For testing the hypothesis of this study, the researcher used paired sample t-test which was calculated by SPSS 17.0. The result shows that there is significant effect of free writing technique on students' writing skills. It can be seen from students’ developments in their writing on recount text. In the pre-test, students found it hard to write a recount text, while in the post-test after treatment, most students can write a recount text. In other words, H1 is accepted. It means that there is a significant effect of free writing technique on students' writing skills. Furthermore, the result of the finding above also shows that free writing technique can improve several things such as students' motivation and self-confidence.